Dissecting the structural basis for the intracellular delivery of OSW-1 by fluorescent probes. Issue 17 (27th March 2017) - Hiraizumi, M.; Komatsu, R.; Shibata, T.; Ohta, Y.; Sakurai, K.
Abstract : Fluorescent derivatives ofOSW-1 and its congeners reveal that the glycosylated cholestane scaffold defines their intracellular destination to the ER and Golgi apparatus. Abstract : The structural basis for the intracellular delivery ofOSW-1 is investigated using fluorescent derivatives ofOSW-1 and its closely related congeners. Despite the large differences in activity, all the fluorescent probes are found to translocate across the plasma membrane to the ER and Golgi apparatus. This observation suggests that the glycosylated cholestane moiety plays an important role in the cell internalization and intracellular localization property ofOSW-1 .